2008
DOI: 10.1080/13561820802054655
|View full text |Cite
|
Sign up to set email alerts
|

Professional differences in interprofessional working

Abstract: UK government policy is encouraging healthcare staff to blur traditional roles, in the drive to increase joint working between practitioners. However there is currently a lack of clarity regarding the impact that changes to traditional working practice might have on staff delivering the services, or on patient care. In this article, we report findings from three qualitative case studies examining joint working practice in stroke care, in which the influence of professional differences was a subsidiary theme. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 26 publications
4
104
0
2
Order By: Relevance
“…High-status professionals may be an obstacle to the interprofessional collaboration adversely, since each group is accorded different interpretive privileges, depending on their status and responsibilities (Abbott, 1998). This type of hierarchical interaction is referred to as ''tribalism'' by Baxter and Brumfitt (2008). Participants remarked the fact that several different professions are involved in planning for each individual can both be an opportunity and an obstacle in individualized care planning.…”
Section: Discussionmentioning
confidence: 99%
“…High-status professionals may be an obstacle to the interprofessional collaboration adversely, since each group is accorded different interpretive privileges, depending on their status and responsibilities (Abbott, 1998). This type of hierarchical interaction is referred to as ''tribalism'' by Baxter and Brumfitt (2008). Participants remarked the fact that several different professions are involved in planning for each individual can both be an opportunity and an obstacle in individualized care planning.…”
Section: Discussionmentioning
confidence: 99%
“…The organizational culture of the settings examined was mainly characterized by insufficient opportunities to have real interdisciplinary work 64 or better transdisciplinary work 65 and nurses often perceived that their autonomy and decision-making processes were restrained by rigid barriers with other professions, especially medicine.…”
Section: Influence Of Workplace Elementsmentioning
confidence: 99%
“…The work of Baxter and Brumfitt (2008) and Jones (2006) denotes the fact that health and social care professionals have their own value base which dictates how they carry out and also accomplish tasks (Carpenter, 2002). As stated earlier, Frost and Robinson (2007 p.191) found that professionals made use of different explanatory frameworks in order to decide upon the task and the nature of the intervention; for example social work practitioners made use of the developmental risk and protection model, health service practitioners the medical model and educationalist an attainment model.…”
Section: Practitioners" (Respondent A)mentioning
confidence: 99%